Development of tractor mounted inter row shielded herbicide sprayer - Gholap, Babasaheb S; Tiwari , Ghanshyam (Journal of Postharvest Technology, 2023)
A six-row tractor mounted inter row shielded herbicide sprayer was developed for weeds control in wide row crops. The different components of the developed sprayer were main frame, chemical tank, spray pump, pressure gauge, control assembly, boom, spray shields, hose pipes, nozzles and power transmission unit. The performance of developed shielded sprayer was evaluated in the field to study the effect of operating pressure (100, 200, 300 and 400 kPa) on volume median diameter (VMD), droplet density (DD) and uniformity coefficient (UC) at different forward speeds (2, 3 & 4 km/h) and different wind velocities (5, 6 and 7 km/h). From the results, it was found that operating pressure had significant effect on volume median diameter, droplet density and uniformity coefficient for all combination of wind velocities and forward speeds.